Environmentally relevant concentrations of the common anxiolytic pharmaceutical oxazepam do not have acute effect on spawning behavior in mature male Atlantic salmon (Salmo salar) parr. (18th November 2019) - Hellström, Gustav; Brodin, Tomas; Jonsson, Micael; Olsen, Håkan; Leander, Johan; Fahlman, Johan; Fick, Jerker; Klaminder, Jonatan
Abstract: Low concentrations of psychiatric drugs are commonly found in surface waters around the world, and their ability to alter behaviors in aquatic fauna has raised concerns about ecological effects. One critical effect that contamination can have in aquatic systems is modifications of reproductive behaviors. In this study, we hypothesized that oxazepam, a common anxiolytic drug and aquatic contaminant previously shown to induce anti‐anxiety behavior in salmonids, also affects the reproductive behavior of Atlantic salmon ( Salmo salar ). To test this hypothesis, small sexually mature Atlantic salmon males (mature parr) were exposed to concentrations of oxazepam comparable to that of effluent water (1.9 µg/L). After 5 days of exposure, their reproductive behavior was compared with that of unexposed control individuals. Behavior was monitored in a large‐scale flume aquarium that also contained a large male and a female to mimic natural spawning conditions for Atlantic salmon. Three behaviors were quantified for the mature parr; (a) amount of courting behavior towards female, (b) proximity to female, and (c) amount of attacks received from the large male. In contrast to our hypothesis, no difference in either courting behavior, proximity to female, or received aggression could be found between exposed and control male parr. Hence, our results indicate that there is no acute effect of the highest levels of oxazepam concentration reported for urban environments on spawning behavior of mature male parr, although chronic effects could not be ruled out.